Development of generic algorithm in wheel-typed hybrid rocket grain design for performance estimation - Kafafy, Raed; Azami, Muhammad Hanafi; Idres, Moumen; Zaharim, Azami; Sopian, Kamaruzaman (2012)
Hybrid rockets are featured by restarting capability, increased safety, high performance and moderate cost. These combined unique characteristics pose then as prominent candidates to replace solid rockets in tactical missiles and launch vehicles in the near future. However, the behavior of hybrid rockets is not fully understood, with issues specifically related to combustion instability and lowered regression rate. To investigate the characteristics of hybrid rocket performance we develop generic algorithm code. This script may serve as a valuable teaching resource in hybrid rocket motor design. This paper uses Hydroxyl Terminated Polybutadiene (HTPB) as a solid fuel and liquid oxygen as an oxidizer for evaluation purposes. Later, we introduce the results of the preliminary design and performance analysis of the hybrid rocket system. An interior ballistic model was used for the analysis of hybrid rocket performance. MATLAB® environment was used to develop the design and performance analysis codes, and visualize the temporal variation of performance characteristics.